Artificial intelligence, engineering systems and sustainable development : driving the UN SDGs - Fowdur, Tulsi Pawan; Rosunee, Satyadev; Ah King, Robert T. F.; Jeetah, Pratima; Gooroochurn, Mahendra (Emerald Publishing Limited, 2024)
Development in any country is impossible if reliable and affordable energy, safe water and sanitation, as well as telecommunication facilities, are not easily accessible. Artificial intelligence and machine learning techniques are now widely used in all branches of engineering to build and optimize systems. The combination of AI and engineering can indeed act as a real catalyst to achieve the UN SDGs. The volume editors present an analysis of different concepts and case studies in engineering disciplines such as chemical, civil, electrical, telecommunications and mechanical engineering, demonstrating how engineering systems and processes can leverage the power of AI to drive and achieve the UN SDGs. Topics covered include sustainable crop production and consumption, AI based clean water and sanitation monitoring, intelligent transport systems and achieving affordable and clean energy through AI and 5G powered internet of energy. Such a study is of paramount importance and is a valuable source of information for researchers, engineers, and policy makers to be able to better design and adopt AI enabled techniques in different engineering areas, with a view to catalyze the achievement of the UN SDGs.
Includes index.
Keywords: Artificial intelligence -- Engineering applications.; Sustainable development.; Business & Economics -- Development -- Sustainable Development.; Artificial intelligence.; elektronické knihy; electronic books